2007
DOI: 10.1212/01.wnl.0000255943.10045.c0
|View full text |Cite
|
Sign up to set email alerts
|

Pilot age and expertise predict flight simulator performance

Abstract: Background-Expert knowledge may compensate for age-related declines in basic cognitive and sensory-motor abilities in some skill domains. We investigated the influence of age and aviation expertise (indexed by Federal Aviation Administration pilot ratings) on longitudinal flight simulator performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 43 publications
17
72
0
Order By: Relevance
“…A multidisciplinary driving test, including a hazard perception component revealed a group of safe drivers identified potential hazards quicker than unsafe drivers (Wood, Horswill, Lacherez, & Anstey, 2013). Longitudinal assessment using a flight simulator revealed that a group of general aviation expert pilots had better flight summary scores and better execution of aviation communications than a group of less skilled pilots (Taylor, Kennedy, Noda, & Yesavage, 2007). A group of expert law enforcement officers shot more accurately and made fewer decision errors than a group of less skilled officers (Vickers & Lewinski, 2012).…”
mentioning
confidence: 98%
“…A multidisciplinary driving test, including a hazard perception component revealed a group of safe drivers identified potential hazards quicker than unsafe drivers (Wood, Horswill, Lacherez, & Anstey, 2013). Longitudinal assessment using a flight simulator revealed that a group of general aviation expert pilots had better flight summary scores and better execution of aviation communications than a group of less skilled pilots (Taylor, Kennedy, Noda, & Yesavage, 2007). A group of expert law enforcement officers shot more accurately and made fewer decision errors than a group of less skilled officers (Vickers & Lewinski, 2012).…”
mentioning
confidence: 98%
“…For over 10 years, we have studied a cohort of aviators aged 40-70 years and more to better understand how their flight simulator performance changes as they approach and pass through their 60s (e.g., Taylor, Kennedy, Noda, & Yesavage, 2007;Yesavage, Taylor, Mumenthaler, Noda, & O'Hara, 1999). The purpose of the present work was to test the hypothesis that baseline cognitive processing speed and pilot expertise predict age-related change in aviator performance.…”
mentioning
confidence: 99%
“…Spearman's Rho indicated that there was not a significant (with 5%) association between total flight hours and pilot age (Spearman's = .430, p = .063). With age, processing speed (how fast the brain works) slows down, and older pilots are no exception from this pattern (Taylor Kennedy, Noda and Yesavage, (2007); Kennedy, Taylor, Reade, and Yesavage (2010). ).…”
Section: Subjectmentioning
confidence: 99%
“…As expected, there was a trend for a positive correlation between flight hours and pilot age. Older pilots typically have had more time to accrue flight hours (Taylor et al, 2007). Analyses revealed that the correlations between (1) the eye tracking parameters and total flight hours and (2) Two case studies were investigated.…”
Section: E Exploratory Analysesmentioning
confidence: 99%